2020
DOI: 10.1186/s12872-020-01534-w
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between overweightness and the extent of coronary atherosclerosis among the South Caspian population

Abstract: Background: Reported effects of obesity on the extent of angiographic coronary artery disease(CAD) have been inconsistent. The present study aimed to investigate the relationships between the indices of obesity and other anthropometric markers with the extent of CAD. Methods: This study was conducted on 1008 consecutive patients who underwent coronary angiography. Body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), and waist-to-height ratio (WHtR) were separately calculated for each pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
3
0
1
Order By: Relevance
“…These findings support 31 they noted that the average BMI of CVD patients was below 25, and they proposed that obesity is a separate risk factor for CVD in both sexes. The results also support, 32 they discovered that a greater risk profile and BMI are both strongly connected with an increased risk of cardiovascular risk factors. 33 It has been found that individuals with a higher BMI have a greater likelihood of being linked to cardiovascular risk factors such as hypertension, hypercholesterolemia, and diabetes mellitus.…”
Section: Discussionsupporting
confidence: 71%
“…These findings support 31 they noted that the average BMI of CVD patients was below 25, and they proposed that obesity is a separate risk factor for CVD in both sexes. The results also support, 32 they discovered that a greater risk profile and BMI are both strongly connected with an increased risk of cardiovascular risk factors. 33 It has been found that individuals with a higher BMI have a greater likelihood of being linked to cardiovascular risk factors such as hypertension, hypercholesterolemia, and diabetes mellitus.…”
Section: Discussionsupporting
confidence: 71%
“…Waist circumference (WC, cm) is regarded as a simple physical measure to assess central obesity, but it does not take into account differences in height and overall body shape. Waist-to-hip ratio (WHR) and waist-toheight ratio (WHtR) have also been associated with increased arterial stiffness, but the relationship is not always significant [8][9][10] . A body shape index (ABSI) and the body roundness index (BRI) are newly developed anthropometric indices.…”
Section: Assessment Of Physical Examination Indices and Blood Biochemical Parametersmentioning
confidence: 99%
“…This is a cross-sectional study conducted among 78 consecutive diabetic patients who underwent coronary angiography for known or suspected coronary atherosclerosis of both sexes aged between 35 and 65 years with significant angiographic findings of >50% diameter stenosis at the cardiac department of a tertiary care hospital with their prior informed consent. The sample size was calculated at a 5% level of significance and 27.86 standard deviations based on the study by Nabati et al, 10 with a 7% margin of error.…”
Section: Selection Of Patientsmentioning
confidence: 99%